The Mechanism of Work of The Mental Lexicon Under the Lights of The Computer System - Parez Khalid Muhammed Amin; Sabah Rasheed Qadir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Abstract of The research entitled (The mechanism of work of the mental lexicon under the lights of the computer system) and the research is an attempt to shed light on the mechanism of the work of the mental lexicon in the mini-program and within the framework of the late opinions of (Chomsky), and it must be said that the dictionary enters the data of the morphological level of the language, and realized Chomsky said that the differences between languages ​​lie mainly in the morphological difference, so the level of analysis in this research is morphological. Introduce it into its context specific to the word. In acquiring any language, there are two mechanisms associated with the completion of the language acquisition project. Decreasing any of the two mechanisms misses the acquirer the opportunity to learn the mother language, which lasts until the age of (9-10) years, and if this period is broken, any deficiency destroys the acquisition. As well as within the framework of the research program, we discuss the issue of moving units and merging units after removing them from the mental lexicon.